Hashtag as a new weapon to resist the COVID-19 vaccination policy: a qualitative study of the anti-vaccine movement in Brazil, USA, and Indonesia - Rizal Khadafi; Achmad Nurmandi; Zuly Qodir; Misran (Taylor & Francis Group, 2022)
In 2019, the World Health Organization (WHO) named the anti-vaccine movement one of the top 10 global health threats. This trend has shown that it can diminish public faith in government and increase public distrust of scientific results in the health sector, including the use of the COVID-19 vaccine. The purpose of this study is to examine the anti-vaccine movement on Twitter social media platform, which uses Hashtag to protest vaccination regulations in the COVID-19 pandemic. The content analysis, relationship analysis, and word cloud analysis models were used in this study, which used a descriptive qualitative approach. The primary data source for this study is Hashtag, which are used to focus on three aspects. First, establish which information in Brazil, the United States, and Indonesia leads the anti-vaccine COVID-19 narrative. Second, how does the Hashtag link between each country work? Third, which narrative dominates the use of Hashtag in each of the three countries? According to the findings of this study, in Brazil, 69.2% of Twitter Hashtag associated to the COVID-19 vaccination were negative, compared to 59.4% in the USA and 62.8% in Indonesia. In general, the Hashtag used in the three countries to oppose COVID-19 vaccination policies have a clear and significant relationship. In Brazil, the Hashtag #covidiots was the most popular, while in the United States, #covivaccine was the most popular, and in Indonesia, #antivaccine was the most popular.